Bamboo Plantations for Phytoremediation of Cadmium in Tannery Effluent: Plant Response and Nutrient Uptake: Life Sciences -Biotechnology - Arumugam, Vidhya; Kalaivani, R. (International Journal of Life Science and Pharma Research, 2023)
The rapid development of the industrial sector led to a greater level of heavy metal Cadmium in recent years. Food and breathing are the primary waysthat Cadmium enters the body. Humans are exposed to long-term health hazards from Cadmium. Cadmium accumulates in immune cells, triggers inflammatoryresponses, and leads to a number of health problems. Compared to conventional physical and chemical techniques, phytoremediation is a useful, environmentallyadvantageous method of remediating contaminated soil. Among the different approaches available for phytoremediation, Phytoextraction is the most effective andsuccessful method since it gets rid of heavy metals. Some bamboo species have been recognized as the most promising species for sequestering carbon andpotentially impacting the phytoremediation of soils contaminated with heavy metals. This study aims to assess the growth patterns of the native Indian bamboospecies (Bambusa bambos, Bambusa vulgaris, and Bambusa balcooa) when exposed to metal-contaminated water, such as tannery effluent, in the Tiruchirappalli area.The ability of bamboo sp. to phytoextract Cadmium from contaminated soil has been demonstrated through experimentation, and its antimicrobial and anti-cancerpotency is tested after being subjected to phytoextraction since the heavy metals in the tannery effluent are predominantly carcinogenic. The laboratory conducteda preliminary study on bamboo plant growth to gauge its growth. To measure the tolerance of bamboo when being rinsed with a solution containing 100 mg Cd/l,the morphological characteristics, heavy metal uptake, and translocation potential of the three bamboo species were assessed. The distribution of Cadmium indifferent fragments of the bamboo plant has also been studied, along with the factors that affect the uptake mechanism. Among the native species, Bambusa bambosis found to have a greater phytoextraction capacity of heavy metals, especially Cadmium. The plant is also evaluated for its anticancer and antimicrobial activitiesfollowing phytoextraction so that the stem and other parts of Bambusa bambos have been used as indigenous medicine by the tribal people, and this could be due tothe presence of flavonoids and other associated compounds present in it.